2008
DOI: 10.1055/s-0028-1087224
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Hearing Improvement in a Patient with an Inflammatory Myofibroblastic Tumor of the Temporal Bone

Abstract: Inflammatory myofibroblastic tumor (IMT) is a rare lesion of unknown etiology and difficult diagnosis. The treatment of IMT is controversial. We report a case of IMT of the temporal bone in a young man presenting with a progressive hearing loss. Three years after diagnosis, partial hearing improvement has been documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Choice of treatment was surgical removal in most of the cases. Galindo et al [7] reported a case of IMT that involved the lateral clivus and petrous bone. An infracochlear approach was adopted to open the petrous apex and successfully remove the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choice of treatment was surgical removal in most of the cases. Galindo et al [7] reported a case of IMT that involved the lateral clivus and petrous bone. An infracochlear approach was adopted to open the petrous apex and successfully remove the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…We identified six reported cases of IMT during this period [6][7][8][9][10][11] . There was a slight male dominant tendency (four cases), and the patients' age varied from 7 to 75 years.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of the patients with orbital IPT that respond to corticosteroids treatment will relapse. The second line of treatment for orbital IPT consists either of low-dose radiotherapy (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Gy at 2 Gy per fraction), chemotherapy, or other immunosuppressive agents. Radiotherapy typically results in 50% or higher long-term local control rates for orbital IPT.…”
Section: Treatmentmentioning
confidence: 99%
“…As for treatments, surgery is usually of the first priority, occurring in 24 reported cases (82.8%). The outcomes are some different among patients: two died of the disease progression soon after the diagnosis [8, 21], two experienced spontaneous improvement without any treatment [18, 22], and the others had subsequently complete or partial remission during the follow up period. Recurrent disease occurred in three of the twenty nine cases (10.3%), and all of them relapsed within a few months after treatment [6, 8, 19].…”
Section: Literature Reviewmentioning
confidence: 99%